Ecosystem Processes Show Uniform Sensitivity to Winter Soil Temperature Change Across a Gradient from Central to Cold Marginal Stands of a Major Temperate Forest Tree - Robert Weigel; Hugh A. L. Henry; Ilka Beil; Gerhard Gebauer; Gerald Jurasinski; Marcin Klisz; Ernst van der Maaten; Lena Muffler; Juergen Kreyling (Ecosystems, 2021)
The magnitude and frequency of soil frost events might increase in northern temperate regions in response to climate warming due to reduced insulation caused by declining snow cover. In temperate deciduous forests, increased soil frost severity can hamper tree growth and increase the mortality of fine roots, soil fauna and microorganisms, thus altering carbon and nutrient cycling. From single-site studies, however, it is unclear how the sensitivities of these responses change along continental gradients from regions with low to high snowfall. We conducted a gradient design snow cover and soil temperature manipulation experiment across a range of lowland beech forest sites to assess the site-specific sensitivity of tree growth and biogeochemical cycling to soil cooling. Even mild and inconsistent soil frost affected tree increment, germination, litter decomposition and the retention of added 15 N. However, the sensitivity of response (treatment effect size per degree of warming or cooling) was not related to prevailing winter climate and snow cover conditions. Our results support that it may be valid to scale these responses to simulated winter climate change up from local studies to regional scales. This upscaling, however, needs to account for the fact that cold regions with historically high snowfall may experience increasingly harsh soil frost conditions, whereas in warmer regions with historically low snowfall, soil frost may diminish. Thus, despite the uniform biotic sensitivity of response, there may be opposing directions of winter climate change effects on temperate forests along continental temperature gradients due to different trends of winter soil temperature.